Effect of different carboxymethyl cellulose structure parameters on tartrates stability of red wine: viscosity and degree of substitution. Issue 7 (2nd July 2020) - Ding, Haiyan; Hou, Ruiting; Li, Yun; Zhang, Beibei; Zhao, Baobao; Liu, Kun
ABSTRACT: The aim of this study was to investigate the effects of carboxymethyl celluloses (CMC) with different structures (viscosity and degree of substitution) on the stability of tartrates as well as the growth mechanism of potassium bitartrate (KHT) crystals. Six CMC samples with different viscosity and degree of substitution were investigated by GPC, XRD and SEM to establish their molecular weight, crystal structure, particle size and molecular morphology. As oenological additives, they were studied in model solution and in Cabernet Sauvignon wine. The tartaric stability and inhibitory efficiency were evaluated by conductivity via mini-contact test and compared with metatartaric acid and mannoproteins commercial additives. The results suggest that under the same degree of substitution (DS), with an increase of viscosity, CMC molecular chains agglomerate and fold, the solubility in the wine decreases, thus the effect of stabilising tartrate deteriorates. Whilst at the same viscosity, with an increase of DS, the charge density of CMC molecules increases and the binding ability of ions increases and thus the stabilising tartrate has an obvious effect. The negative charge on the −COO− groups extended from CMC polymer tends to repulse the HT − group in solution while attracting K + ions to produce a concentration gradient at the crystal surface. In addition, CMC complexes with K + ions in solution, reducing the number of K + ions able to diffuse to the adsorption layer. Generally, CMC-6 with a higher the degree of substitution and lower viscosity had best application effect on tartrate stabilisation, and from the price and application performance, CMC was found to be superior to commercial additives like metatartaric acid and mannoproteins.